(untitled) (Academicia Globe: Inderscience Research, 2021)
This article discusses the assessment, prevention and management of financial risks affecting the activities of foreign banks using digital technologies. At the same time, the methods of preventing financial risks using the most modern methods of digital technologies in the practice of international banks are studied.